RETRACTED: Energy Efficient Digital Omnichannel Marketing Based on a Multidimensional Approach to Network Interaction - Barykin, Sergey Evgenievich; Sergeev, Sergey Mikhailovich; Provotorov, Vyacheslav Vasilyevich; Lavskaya, Kristina Konstantinovna; Kharlamov, Andrey Viktorovich; Kharlamova, Tatiana Lvovna (Frontiers in Energy Research, 2022)
This paper measure digital Omni marketing and th digital economy to drive green development. Two methodologies are used to construct the model. The methods of digital marketing involve alternative channels of interaction and energy efficiency by including a mathematical apparatus for analyzing multi-dimensional structures (n-D structures). In the econometric model, direct and mediating effects are checked. Also, the regression analysis shows the influence of technological innovation and the digital economy on energy efficiency. Furthermore, spillover effects from the digital economy might affect high-quality green development in emerging countries. Topology objects characterize participants in the digital customer value creation network. Algorithms preprogrammed in cloud servers of the nodes determine the quality of the implementation of system interaction in omnichannel marketing. It is believed that competition has transformed into a contest of online platforms in energy efficiency and economic efficiency. It is emphasized that there is no alternative to multichannel interaction at the present stage of implementing digital business solutions. The lack of an approach to the formation of "seamless" ways of interaction through available communication channels between an organization and a consumer is noted in the analyzed works of Russian and foreign researchers that address the development of digital marketing and multichannel network interaction. Researchers have developed omnichannel interaction algorithms based on mathematical models. The proposed approach supplements the digital twin model with economic indicators and methods. Decisions that form the basis of the software should be found in the application of a scientific approach using optimization methods and mathematical models. Analyzing multi-dimensional structures allows for omnichannel network digital interaction and improves the digital marketing approach.